Integrated weed control (chemical & mechanical) in chickpea (Cicer arietinum L.) under Shoushtar conditions - adel modhej; zahra alikhani galeh (پژوهش‌های حبوبات ایران)
Introduction Chickpea is a poor competitor to weeds because of slow growth rate and limited leaf area development at early stages of crop growth and establishment. Crop yield loss could be be in high extent due to increasing of weed biomass, weed density and weed species. Chickpea yield losses due to weed competition have been estimated to range between 40 and 87% depending on weed species and density. Herbicides play a key role in weed control and are used extensively today. The current tendency in chickpea weed control in the Mediterranean region is to shift from the costly manual mechanical energy to the chemical energy through more usage of effective herbicides particularly with the increased adoption of winter sowing. Several herbicides with different mode of action such as Trifloralin (Treflan) and Pendimetalin (Prowl) are used for weed control in chickpea farms. Nevertheless herbicide application may have several important environmental issues. These include unintended damage occurring both on the sprayed site, and offsite. Herbicide use also injures the human and animals. Integrated weed management (IWM) is the most important strategies to avoid herbicide environmental issue and increasing inputs productivity. Furthermore, integrated weed management strategies attempt to limit the deleterious effects of weed growing on crop plants. The present report describes the effect of integrated methods on weed density and grain yield of chickpea under Shoushtar conditions.